2023
DOI: 10.3389/fnins.2023.1131916
|View full text |Cite
|
Sign up to set email alerts
|

The increased functional connectivity between the locus coeruleus and supramarginal gyrus in insomnia disorder with acupuncture modulation

Abstract: BackgroundInsomnia disorder (ID) seriously affects the quality of people’s daily life, and acupuncture is an effective therapy for it. As an essential component of the upward activation system, the locus coeruleus (LC) plays a crucial role in sleep–wake regulation, its aberrant functional connectivity (FC) is found to be involved in ID. The purpose of this study was to explore the modulation effect of acupuncture on the resting state FC of LC in ID patients.Methods60 ID patients were recruited and randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…A total of 21 studies compared the efficacy of acupuncture with that of sham acupuncture ( 27 , 60 , 76 , 84 , 113 – 129 ). The overall meta–analysis result showed that acupuncture had better efficacy for treating insomnia (MD: −4.19, 95% CIs: −5.33 to −3.05, I 2 =93%, P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies compared the efficacy of acupuncture with that of sham acupuncture ( 27 , 60 , 76 , 84 , 113 – 129 ). The overall meta–analysis result showed that acupuncture had better efficacy for treating insomnia (MD: −4.19, 95% CIs: −5.33 to −3.05, I 2 =93%, P < 0.01).…”
Section: Resultsmentioning
confidence: 99%